2000
DOI: 10.1007/bf03354449
|View full text |Cite
|
Sign up to set email alerts
|

The compliance of hypocaloric diet in type 2 diabetic obese patients: A brief term study

Abstract: In studies of the effect of diets in obese type 2 diabetic patients, information about the degree of compliance or non-compliance is generally lacking or incomplete, though their poor long-term success rate is widely recognized. We have quantified the degree of short-term compliance with a personalized hypocaloric diet (800-1500 kcal) in 77 obese type 2 diabetic patients (mean age 60, mean BMI 34.4) three months after explaining their dietary schedule and its expected advantages by means of simple but essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, to our knowledge, this is the first in vivo study to investigate the effect of dietary fatty acid composition on the insulin signaling pathway and subsequent GLUT4 translocation in skeletal muscle for a type 2 diabetic status under conditions of a high-fat diet. Considering the reality that the majority of diabetic patients fail to reduce the amount of fat or calories in their diet [20][21][22], this study provides meaningful information that a MUFA-enriched diet could allow diabetic patients to maintain insulin sensitivity even if they continue to consume a high-fat diet.…”
Section: Discussionmentioning
confidence: 98%
“…However, to our knowledge, this is the first in vivo study to investigate the effect of dietary fatty acid composition on the insulin signaling pathway and subsequent GLUT4 translocation in skeletal muscle for a type 2 diabetic status under conditions of a high-fat diet. Considering the reality that the majority of diabetic patients fail to reduce the amount of fat or calories in their diet [20][21][22], this study provides meaningful information that a MUFA-enriched diet could allow diabetic patients to maintain insulin sensitivity even if they continue to consume a high-fat diet.…”
Section: Discussionmentioning
confidence: 98%
“…2006). Diabetic patients have reported that they consume 40–50% more calories than the recommended diet (Zilli et al. 2000) and a higher intake of carbohydrates is associated with increased triglyceride (TG) concentrations (Peveler et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, clients with diabetes are more likely to be obese and physically inactive than the non-diabetic population (Adeqhate et al 2006). Diabetic patients have reported that they consume 40-50% more calories than the recommended diet (Zilli et al 2000) and a higher intake of car-bohydrates is associated with increased triglyceride (TG) concentrations (Peveler et al 2005). Most of these findings are based on studies of individuals from Western cultures; dietary patterns of eastern cultures, such as Korean, have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic surgery can be an attractive option for patients with diabesity, especially if performed before the stage at which irreversible beta-cell insulin secretory failure ensues. One advantage of metabolic surgery is that maintenance of weight-loss (which is particularly difficult to achieve through lifestyle modification in patients with diabesity) is often achievable with this treatment modality [61]. In addition to being an effective means of promoting weight loss, metabolic surgery also often results in improvements to glycaemic control in patients with diabesity.…”
Section: Surgical Approaches To Management Of Diabesitymentioning
confidence: 99%